The re-establishment of Luehea macrophylla (Malvaceae, Grewioideae) - Gerace, Samuele; A. Baumgratz, José Fernando; Bovini, Massimo G. (Phytotaxa, 2024)
The nomenclature of the species Luehea macrophylla Pohl is reinstated in this study, drawing on distinctive features such as epicalyx bracts, petals, ovary characteristics, and novel diagnostic fruit characters. The information, including new synonyms and distributional data, complemented by the examination of relevant specimens, is provided. Furthermore, a comparative analysis of morphology is presented, offering insights into the distinguishing characteristics of L. macrophylla when compared to its congeners.